Amyloid tracers binding sites in autosomal dominant and sporadic Alzheimer's disease. Issue 4 (28th September 2016) - Ni, Ruiqing; Gillberg, Per‐Göran; Bogdanovic, Nenad; Viitanen, Matti; Myllykangas, Liisa; Nennesmo, Inger; Långström, Bengt; Nordberg, Agneta
Abstract : Introduction: Amyloid imaging has been integrated into diagnostic criteria for Alzheimer's disease (AD). How amyloid tracers binding differ for different tracer structures and amyloid‐β aggregates in autosomal dominant AD (ADAD) and sporadic AD is unclear. Methods: Binding properties of different amyloid tracers were examined in brain homogenates from six ADAD with APPswe, PS1 M146V, and PS1 EΔ9 mutations, 13 sporadic AD, and 14 control cases. Results: 3 H‐PIB, 3 H‐florbetaben, 3 H‐AZD2184, and BTA‐1 shared a high‐ and a varying low‐affinity binding site in the frontal cortex of sporadic AD. AZD2184 detected another binding site (affinity 33 nM) in the frontal cortex of ADAD. The 3 H‐AZD2184 and 3 H‐PIB binding were significantly higher in the striatum of ADAD compared to sporadic AD and control. Polyphenol resveratrol showed strongest inhibition on 3 H‐AZD84 binding followed by 3 H‐florbetaben and minimal on 3 H‐PIB. Discussion: This study implies amyloid tracers of different structures detect different sites on amyloid‐β fibrils or conformations. Highlights: In the present study, binding properties of different amyloid‐beta (Aß) tracers have been studied in postmortem brain tissue from autosomal dominant Alzheimer's disease (ADAD) as well as sporadic Alzheimer's disease (sAD). The studied Aβ tracers showed multiple binding sites and different binding properties in ADAD in comparison to sAD brain. By using AZD2184, a third Aβ binding site was detectable in the ADAD frontal cortex. High binding of the Aβ tracers in ADAD striatal tissue suggests conformal differences of amyloid aggregates in ADAD compared to sAD, confirming earlier in vivo PET observations in the cortex and striatum of sAD and ADAD patients. The antiamyloid phenol compound resveratrol interacted in nanomolar range with AZD2184 while with lower affinity with florbetaben and lowest with PIB. Understanding the binding mode of different amyloid tracers to brain Aβ aggregates may facilitate the development of new early biomarkers as well as Aβ‐targeting drug therapies.